20 The preventive effect of an adductor strengthening programme on groin problems among male football players: a cluster-randomised controlled trial. (19th April 2018) - Harøy, Joar; Clarsen, Ben; Wiger, Espen Guldahl; Øyen, Mari Glomnes; Serner, Andreas; Thorborg, Kristian; Hölmich, Per; Andersen, Thor Einar; Bahr, Roald
Abstract : What's cutting edge in sports medicine?, Norway, februar 2, 2018, 16:45 – 18:00. Introduction: Groin problems are highly prevalent in male football players. Previous groin-specific prevention programs have shown no effect on groin injury rates. However, a single-exercise approach targeting hip adduction strength has not been tested previously. Aim: Evaluate the effect of a single-exercise approach, based on the Copenhagen Adduction exercise, to reduce the high prevalence of groin problems in male players. Materials and methods: 35 semi-professional Norwegian senior football teams were cluster-randomised (18 teams, 339 players in the intervention group, 17 teams 313 players in the control group) and followed for 1 full season. An adductor strengthening programme, with three progression levels, was introduced to the intervention group to perform 3 times weekly during pre-season and once weekly during the competitive season. The main outcome measure, prevalence of groin problems, was measured weekly for 28 weeks during the competitive season using the Oslo Sports Trauma Research Centre Overuse Injury Questionnaire. Result: The average prevalence of groin problems during the season was 13.5% (95% CI: 12.3% to 14.7%) in the intervention group, and 21.3% (95% CI: 20.0% to 22.6%) in the control group. This corresponds to a 41% (OR 0.59, 95% CI: 0.40 to 0.86, p=0.008) lower risk of reporting groin problems for players performing the adductor strengthening programme. Conclusion: The adductor strengthening programme reduced the prevalence and risk of groin problems among male football players, and should therefore be implemented in male football teams.